2021
DOI: 10.1161/jaha.120.020654
|View full text |Cite
|
Sign up to set email alerts
|

The Gut Microbiome of Heart Failure With Preserved Ejection Fraction

Abstract: Background Risk factors for heart failure with preserved ejection fraction (HFpEF) include hypertension, age, sex, and obesity. Emerging evidence suggests that the gut microbiota independently contributes to each one of these risk factors, potentially mediated via gut microbial‐derived metabolites such as short‐chain fatty acids. In this study, we determined whether the gut microbiota were associated with HFpEF and its risk factors. Methods and Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 34 publications
3
37
1
Order By: Relevance
“…A longitudinal study of 25 human mother-infant pairs showed substantial early seeding of the infant gut microbial communities from strains present in the maternal gut. 25 Our study supports that the acquisition and development of the infant microbiome is seeded early in life, is dependent on the maternal diet during pregnancy, and persists into later life. Our findings advance this concept by demonstrating maternal fibre intake profoundly impacted offspring gut microbial taxonomy and function, supporting the notion that early life dietary exposure shapes later life microbial ecology.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…A longitudinal study of 25 human mother-infant pairs showed substantial early seeding of the infant gut microbial communities from strains present in the maternal gut. 25 Our study supports that the acquisition and development of the infant microbiome is seeded early in life, is dependent on the maternal diet during pregnancy, and persists into later life. Our findings advance this concept by demonstrating maternal fibre intake profoundly impacted offspring gut microbial taxonomy and function, supporting the notion that early life dietary exposure shapes later life microbial ecology.…”
Section: Discussionsupporting
confidence: 79%
“…23 Clinical and preclinical studies have identified distinct microbial signatures with fibre intake 24 that are evident in CVD, such as heart failure. 25 The gut microbial ecology is readily adaptable by dietary manipulations such as fibre. 26 To determine the influence of maternal fibre intake on the offspring’s gut microbial composition, we first sequenced the bacterial 16S rRNA from caecal content collected from female C57BL/6J dams and their offspring.…”
Section: Resultsmentioning
confidence: 99%
“…Certain diseases and the gut microbiome interact in people with heart failure. In a study of the gut microbiota of patients with chronic heart failure, it was discovered that patients with congestive heart failure have particular fundamental bacterial imbalances (74). Congestion of the splanchnic circulation, edema of the intestinal wall, and impaired intestinal barrier function all result in bacterial translocation and bacterial products entering the systemic circulation, aggravating the inflammatory response and promoting the progression of heart failure and atherosclerosis (75).…”
Section: Heart Failurementioning
confidence: 99%
“…Changes in the composition of GM in HF have been confirmed not only in the clinical study but also in experimental animal studies, which helped elucidate the role that microbiota played in the development of HF ( 14 , 15 , 29 ). Table 1 summarizes the several cohort studies that have demonstrated the GM alterations in HF patients ( Table 1 ) ( 15 , 25 , 27 , 30 – 33 ).…”
Section: Gut Microbiota Alterations In Heart Failurementioning
confidence: 99%
“…More recently, Kummen et al identified microbiota changes in 15 taxa, including depletion of taxa in the Lachnospiraceae family, which are known producers of butyrate ( 32 ). Another study showed that HFpEFs had a lower Firmicutes -to- Bacteroidetes ratio but not significantly and depleted bacteria that are short-chain fatty acid producers ( 33 ). Additionally, there has been evidence that Bacteroides fragilis and Ruminococcus had a positive effect on HF ( 41 ).…”
Section: Gut Microbiota Alterations In Heart Failurementioning
confidence: 99%